Minimum Wage and Tax Evasion: Theory and Evidence - Mirco Tonin (Hungarian Academy of Sciences, Institute of Economics, 2007)
The paper investigates the role of the minimum wage in a competi- tive economy in which there is underreporting of earnings by employed labour. The minimum wage induces higher compliance by some low- productivity workers and transforms a nominally neutral .scal system into a regressive one. A spike in the wage distribution at the mini- mum wage level appears and a positive correlation between the size of the spike and the size of the informal economy is predicted and documented using cross-country data for Europe. A further result is that employees whose officially declared earnings appear to be boosted by a minimum wage hike actually experience a decline in their true income. This prediction finds support in an empirical test using the massive increase in the minimum wage that took place in Hungary in 2001 as a quasi-natural experiment.
Keywords: J38; H26; H32; P2; 330; Minimum Wage; Tax Evasion; Wage Distribution; Hungary; Mindestlohn; Steuervermeidung; Schattenwirtschaft; Lohnstruktur; Ungarn